Analisis Potensi Financial Distress Industri Pertambangan di Asia Tenggara - Dinda Azzahra; Yunus Harjito; Agus Endrianto Suseno (ITB AAS Indonesia Surakarta, 2021)
The purpose of this study is to analyze the effect of profitability ratio, liquidity ratio, leverage ratio, and operating capacity ratio on financial distress potential. The population in this study are mining companies listed on the Asia Tenggara Stock Exchange in the period 2017-2019. The sample in this study amounted to 140 samples obtained from 84 companies for 3 years with a purposive sampling method. The analysis technique in this study is panel data regression analysis using eviews 9. The results showed that profitability did no influenced the finacial distress potential, liquidity ratio did no influenced the finacial distress potential, leverage ratio did no influenced the finacial distress potential, and operating capacity ratio has a negative effect on finacial distress potential.